Analysis in calculating Osseo dental discrepancy manually and in I Model Analysis 2 application - Santiesteban-Ponciano, Fabián Alejandro (2016)
Objective: Determine whether there is a difference between the calculation of the discrepancy osseoden-tal manually and using the iModelanalisys2 application. Materials and method: A convenience sample of 120 models pretreatment orthodontic study was formed. We proceeded to perform the measurement of all dental organs of the upper and lower arch, and the total length of both arches with a digital caliper and calculator. Subsequently, the calculation discrepancy oseodental entering the data obtained in the iModelAnalysis2 application in a smartphone. Results: The average age of the sample was 17 years. In the maxillary average dental bone discrepancy to manually calculate it was -3.7mm and calculate the average program iModelAnalysis2 dental bone discrepancy was -3.22mm. In the mandible, the diffe-rence between using the application and do it manually discrepancy of 0.5mm. When comparing the results using Student’s t test, no statistically significant differences were found. Conclusions: Realising the calculation of the osseodental discrepancy manually or using the smartphone application iModela-nalisys2 not alter jthe diagnosis.